Impact of minerals freight and logistic operation towards traffic safety in Kuantan road network - Nik Noranis Syazlin, Nik Abd Razak (2019)
Mineral resources are the key implications in the economic growth in Malaysia. Minerals are divided into two major categories namely metallic and non-metallic. This study focuses on metallic mineral specifically bauxite as Malaysia, particularly Kuantan, Pahang was one of the world’s top bauxite producer with the biggest mining pits in between year 2014 and 2016. Pahang government faced various transportation issues related to minerals mining operations especially in road safety aspect which includes an increase in the number of road traffic crash involving minerals vehicle’s freight. In defining the crash prone area related to mineral vehicle’s freight, traffic crash statistics involving heavy vehicles along mineral’s mining pits and Kuantan Port were obtained from Traffic Unit, Royal Malaysia Force Pahang. Audit checklist was developed for auditing the crash prone area at selected road stretches using Guidebook for Traffic and Road Safety Audit (Metra). The results show that the condition of traffic infrastructures from surface distress, traffic sign and marking analysis at various locations were found to be inadequate where the road users tend to involve in traffic crash. Thus, suitable remedial measures are suggested to improve the road’s level safety.